25 problems for STEM education - Ochkov, V. F. (Valeriĭ Fedorovich) ([S.l.] : CRC PRESS, 2020)
25 Problemsfor STEM Education introduces a new and emerging course for undergraduate STEM programs called Physical-Mathematical Informatics. This course corresponds with the new direction in education called STE(A)M (Science, Technology, Engineering, [Art] and Mathematics). The book focuses on undergraduate university students (and high school students), as well as the teachers of mathematics, physics, chemistry and other disciplines such as the humanities. This book is suitable for readers who have a basic understanding of mathematics and math software. Features Contains 32 interesting problems (studies) and new and unique methods of solving these physical and mathematical problems using a computer as well as new methods of teaching mathematics and physics Suitable for students in advanced high school courses and undergraduates, as well as for students studying Mathematical Education at the Master's or PhD level One of the only books that attempts to bring together ST(E)AM techniques, computational mathematics and informatics in a single, unified format
OCLC-licensed vendor bibliographic record.
Keywords: Computer science -- Study and teaching; Mathematics -- Study and teaching; Physics -- Study and teaching; Information technology -- Study and teaching; COMPUTERS / Mathematical & Statistical Software; MATHEMATICS / Applied; MATHEMATICS / General